Control over Vortex Shedding and Drag Force on a Circular Obstacle Using a Pair of Downstream Splitter Plates in a Transient Flow. (21st February 2023) - Ain, Qurrat Ul; Mahmood, Rashid; Abbasi, Waqas Sarwar
Abstract : The current work is an analysis of the laminar, two-dimensional, and transient flow over a circular cylinder with a two-branched splitter plate. For complex nonlinear governing equations, the finite element method is used as a computational approach. The objective of the current study is to determine the best conditions using geometrical characteristics along with the impact of Reynolds number R e .The geometric parameters, α which is the angle of separation between the pair of splitter plates of length L and G / D which is the gap from diameter ratio of the splitter plate to cylinder diameter, are the controlling tools for the present study. Due to its little impact on flow characteristics, it was discovered that using a two-branched splitter plate in Reynolds numbers under 100 is not desirable. A complete vortex shedding has been achieved with α = 0 ° and G / D = 2 at R e = 100 and also the periodic behavior of velocity has been controlled. The least drag force is observed at an angle of 30 ° between the two plates compared to another angle of 0 ° . It is not advised to use two splitter plates at angles more than 30 ° because this will not further contribute in the drag reduction. Since the gap to diameter ratio between the splitter plates and the cylinder increased up to a significant value, the overall control on hydrodynamic effects is achieved. It is concluded that the maximum drag reduction of 48% over the cylinder has taken place when the R e i s 200, α i s 30 °, a n d G / D i s 2 .